2017
DOI: 10.1007/s00404-017-4463-0
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up after radical vaginal trachelectomy (RVT): patients’ problems and physicians’ difficulties

Abstract: Follow-up of patients after RVT needs special expertise because the symptoms differ from those after hysterectomy and examinations ensuring oncologic safety require special attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…However, radical trachelectomy has some morbidities. Removal of unnecessary endocervical canal may lead to cervical stenosis in those patients [7]. Abortion and second trimester miscarriages are more than 70% in patients underwent abdominal radical trachelectomy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, radical trachelectomy has some morbidities. Removal of unnecessary endocervical canal may lead to cervical stenosis in those patients [7]. Abortion and second trimester miscarriages are more than 70% in patients underwent abdominal radical trachelectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Abortion and second trimester miscarriages are more than 70% in patients underwent abdominal radical trachelectomy. In addition, parametrectomy is responsible for the majority of surgical complications such as intraoperative significant blood loss, bladder and bowel dysfunction, fistula formation, and sexual dysfunction [7,8]. On the other hand, very low rate of parametrial involvement and recurrence in patients with cervical tumor ≤ 2 cm has been reported in many studies [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In this case, menstruation had stopped owing to the MPA therapy, which may have made cervical stenosis more likely to occur owing to the lack of menstrual blood drainage. Intrauterine devices are reported to prevent cervical stenosis after RT and should be actively considered in cases where cervical stenosis is a problem, as in this case 14,15 …”
Section: Discussionmentioning
confidence: 97%
“…Intrauterine devices are reported to prevent cervical stenosis after RT and should be actively considered in cases where cervical stenosis is a problem, as in this case. 14,15 The patient overcame the two diseases and gave birth to a son, but the possibility of recurrence still exists. AEH can recur even after remission and a live (c) The infant's head had descended so far that the shoulder and arm were visible just below the uterine incision.…”
Section: Discussionmentioning
confidence: 99%
“…Following these findings, accurately selecting patients who wish to preserve fertility for either radical trachelectomy or more conservative approaches is of increasing clinical importance. As evidence of oncologic and obstetrical outcomes following radical abdominal trachelectomies in Germany and Austria is currently limited, and only few tertiary care centers in Central Europe perform the procedure, the present study aimed to retrospectively assess patients who underwent radical abdominal trachelectomies at the Department of Obstetrics and Gynaecology, Medical University of Vienna, Austria, over a timeframe of 10 years and contextualize outcomes and patient selection according to more recently proposed “low-risk” criteria [ 15 ].…”
Section: Introductionmentioning
confidence: 99%